‘Why is it that a photograph always looks clear and sharp, — not at all like a Turner?’ John Ruskin & Perceptual Aberration - Lawrence Gasquet (Cahiers Victoriens et Edouardiens)
The presence of the camera becomes prominent among scientific and artistic discourses of the 19th century; it is also fundamental to John Ruskin’s aesthetic theory, as a close study of several of his writings shows. Photography reveals for instance the existence of some physiological distortions in human perception, and perceptual aberration was analysed at great length by John Ruskin, whether it be revealed by Turner’s art or by the daguerreotypist’s talent or lack of skill. In volume IV of Modern Painters, Ruskin contends that photographs might after all be more on Turner’s side than he and other critics might have first thought: ‘Photographs never look entirely sharp; but because clearness is supposed a merit in them, they are usually taken from very clearly marked and un-Turnerian subjects; and such results as are misty and faint, though often precisely those which contain the most subtle renderings of nature, are thrown away, and the clear ones only are preserved. Those clear ones depend for much of their force on the faults of the process. Photography either exaggerates shadows, or loses detail in the lights . . . and misses certain of the utmost subtleties of natural effect (which are often the things that Turner has chiefly aimed at,) while it renders subtleties of form which no human hand could achieve’. (Ruskin, 1856, vol. IV, Chapter IV, §11).I shall strive to define in this paper some of the implications of the act of vision according to Ruskin, wondering about differences in effect and form for instance, and seeking their causes; I will attempt to show how some of the obstacles which can actually hamper human sight turn out to be eminently positive for Ruskin, giving birth to the main arguments of his belief in the superiority of Medieval art over Renaissance art. Ruskin’s defence of imperfection thus appears to be closely linked to natural perceptual aberration.